Peran Fisioterapi Pada Individu Dengan Hemiparesis Sinistra Post Stroke : A Case Study - Diajeng Sabina Purwagayatri; Adnan Faris Naufal; Nur Indah Swariningrum (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
Introduction: Stroke occurs when the blood supply to the brain is blocked and blood vessels in the brain burst. The brain can't get the blood and oxygen it needs, so brain cells die. In this case, the patient complained of a feeling of weakness and heaviness in the left side of the body, which made it difficult for him to carry out everyday activities. Objective: To determine the role of physical therapy in individuals with left hemiparesis after stroke on muscle strength, spasticity, and functional ability using infrared intervention, electrical stimulation, and exercise therapy. Method: Subjective and objective examinations were carried out, followed by physiotherapeutic intervention in 3 weeks. Results: After physiotherapeutic intervention, the results showed an increase muscle strength using manual muscle testing (MMT) of the hip muscle group T1=2 to T3=2+, the knee muscle group T1=2 to T3=-3. Reduced muscle tone according to the Asworth scale in the shoulder area T1=1+ to T3=1, as well as functional ability according to the Barthel index with results from T1=65 to T3=70. Conclusion: Physiotherapeutic interventions using infrared, electrical stimulation, and exercise therapy can increase muscle strength, reduce spasticity, and improve functional ability in individuals with left-sided hemiparesis after stroke